2016
DOI: 10.2166/wst.2016.414
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment plant effluent as a source of microplastics: review of the fate, chemical interactions and potential risks to aquatic organisms

Abstract: Wastewater treatment plant (WWTP) effluent has been identified as a potential source of microplastics in the aquatic environment. Microplastics have recently been detected in wastewater effluent in Western Europe, Russia and the USA. As there are only a handful of studies on microplastics in wastewater, it is difficult to accurately determine the contribution of wastewater effluent as a source of microplastics. However, even the small amounts of microplastics detected in wastewater effluent may be a remarkable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(108 citation statements)
references
References 88 publications
2
90
0
1
Order By: Relevance
“…Small numbers per litre released in effluent can translate to large numbers of plastics in aquatic systems, considering the large volumes of treated effluent released from WWTPs worldwide. As a result, studies have shown that wastewater effluent is a source of microplastics to aquatic systems (see reviews in Estahbanati and Fahrenfeld 2016;Ziajahromi et al 2016). …”
Section: Open Accessmentioning
confidence: 99%
“…Small numbers per litre released in effluent can translate to large numbers of plastics in aquatic systems, considering the large volumes of treated effluent released from WWTPs worldwide. As a result, studies have shown that wastewater effluent is a source of microplastics to aquatic systems (see reviews in Estahbanati and Fahrenfeld 2016;Ziajahromi et al 2016). …”
Section: Open Accessmentioning
confidence: 99%
“…MPs are dispersed into the ocean all over the world. Often detected in beaches (Herrera et al 2017;Imhof et al 2018;Naji et al 2017), seabed sediments (Karlsson et al 2017;Van Cauwenberghe et al 2013), wastewater effluents (Magnusson and Norén 2014;Murphy et al 2016;Ziajahromi et al 2016), surface waters (Eriksen et al 2013;La Daana et al 2017), freshwater systems (Horton et al 2017b) and even sea ice in the Arctic (Lusher et al 2015;Obbard et al 2014;Waller et al 2017), and the Antarctic (Waller et al 2017) transported by ocean and wind. MPs also have been observed in the atmosphere, as well as in indoor and outdoor environments (Dris et al 2017;Gasperi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, consumers may adequately dispose of waste products with the intention of items reaching recycling or landfill facilities, but adverse weather conditions can displace items into the environment. In the case of microplastics generated from consumers, through the use of cosmetics and personal care products containing microbeads or washing synthetic clothing, small plastics can pass through wastewater treatment plants depending on the sophistication of the equipment, number of treatment stages and procedures used (Napper et al, 2015;Ziajahromi et al, 2016;Mahon et al, 2017).…”
Section: Plastic Production and Waste Managementmentioning
confidence: 99%